An enhanced 3D data transfer method for fluid–structure interface by ISOMAP nonlinear space dimension reduction. (May 2015) - Li, Li-zhou; Zhang, Jun; Zhao, Jun-li; Yue, Zhu-feng
Highlights: The impact of self-parallel interfaces on the accuracy of the data transfer methods is investigated. A method is proposed to transfer data through the planar projection spaces. A new technique is set up to project 3D interfaces into the planar space by an ISOMAP nonlinear dimensionality reduction. The proposed method is compared with some methods in a pressure transfer of a turbine blade. Abstract: With the accuracy limitation of some transfer methods in the self-parallel fluid–structure interfaces, a data transfer method is proposed by an ISOMAP (Isometric Mapping) nonlinear dimensionality reduction. Through this new method, the data transfer problem of the self-parallel interfaces is solved. Example of a 3D turbine blade shows that the proposed method can improve the transfer accuracy in the non-matching meshes.